Ultrasound-guided microsurgical excision for brachial plexus schwannomas: short-term clinical study - Yuce, Ismail; Kahyaoglu, Okan; Mertan, Pelin; Cavusoglu, Halit; Aydin, Yunus (Turkish neurosurgery, 2019)
AIM: To describe the ultrasound-guided microsurgical excision technique and to evaluate the surgical outcomes of brachial plexus schwannomas. MATERIAL and METHODS: Eleven patients who underwent ultrasound-guided microsurgery for small (<3 cm) brachial plexus schwannomas between 2013 and 2017 were included in our study. RESULTS: The mean age of the patients was 45 years (range: 30-68 years), with six tumors localized on the right and five on the left side. There were no perioperative or postoperative complications. No postoperative deficits were observed in the patients. CONCLUSION: Surgeons can safely and completely excise most of the benign (<3 cm and non-palpable) brachial plexus tumors by the ultrasound-guided microsurgical excision technique.